Caracterização e aspectos etnobiológicos da pesca artesanal nas comunidades do litoral sul de João Pessoa, Paraíba - Pedro, Carmem Karime Bacalháo (2016)
The artisanal fishing is a secular activity developed by men and characterized by small scale exploitation of fisheries that serves as family income and subsistence. Currently, the coastal marine environment of Brazil has been suffering substantial degradation processes, due to the growing anthropic pressure and over-exploitation of natural resources. In the State of Paraiba, relevant studies suggest significant declines in fish catches by artisanal fisheries. Thus, the development of fisheries management plans that involve the interests of all individuals is critical, aiming the sustainability of fisheries. To achieve this, it is necessary to prioritize the use of Traditional Ecological Knowledge (TEK) of the local fishing communities, which is characterized as a set of knowledge and practices developed through adaptive processes in the relationship of living beings and the environment. Therefore, this study aims to characterize the artisanal fishing of Penha and Ponta do Seixas communities, located in Joao Pessoa, Paraiba State, through the description of their ethno-ecological aspects and the possible relationship between the amount of fish caught and overfishing. Artisanal fishery communities of Penha and Ponta do Seixas, located in the south of João Pessoa coast, in Paraíba state, were characterized by the use of scientific knowledge and Traditional Ecological Knowledge (TEK) of local fishermen. The TEK proved to be essential in the data collection, perception of fish stocks, and overfishing of certain species. The study was conducted through landing reports, unstructured interviews, participant observation, structured, and semi structured interviews. Motorized boats were the main vessels used by fishermen. Eight different fishing strategies have been identified, and the most used were the handline and bottom gillnet. Fifty three species of fishes were recorded, 24 through the monitoring of landings (captured with handline) and 29 from interviews. In total 7,670.4kg of fishes were sampled in 28 landings between February 2015 and January 2016. Among the 27 recorded families: Carangidae, Lutjanidae, and Serranidae stood out. The most captured species were: ‘guarajuba’ (Carangoides bartholomaei), ‘arabaiana’ (Seriola dumerili); ‘peixe-rei’ (Elegatis bipinnulatus), and ‘xixarro’ (Carangoides crysos). Most of landings were recorded during the summer, although no significant differences were observed between biomass and species richness captured during summer and winter. It was proposed the Index of the Fishery Importance (IPP) in order to highlight species, according to their biological, ecological, and commercial characteristics, that are more valued in the studied communities. According to the criteria of the IPP, five species stood out: ‘guarajuba’ (Carangoides bartholomaei), ‘arabaiana’ (Seriola dumerili), ‘xixarro’ (Carangoides crysos), ‘cioba’ (Lutjanus analis), and ‘peixe-rei’ (Elegatis bipinnulatus). Furthermore, it was used the Smith’s salience index (IS), which is based on higher frequency values and coincidence of items, by which: ‘cioba’ (Lutjanus analis), ‘guarajuba’ (Carangoides bartholomaei), ‘cavala’ (Scomberomorus cavalla), ‘xixarro’ (Carangoides crysos), and serra (Scomberomorus brasiliensis) stood out. In order to get more information on the biology, ecology and fisheries aspects of these species, an ethnobiological study was conducted with local fishermen. It was observed that fishermen have a vast knowledge of fish species, especially those considered most important according to the values of the IPP and IS. Therefore, it is suggested that fishermen’s TEK should be used in aid of scientific research conducted in the region as well as in discussion of fisheries resources management that may be developed in the area.